Analisis Dampak Asap Pabrik Industri PT Multi Energi Biomassa terhadap Kondisi Masyarakat Sekitar - Rifai, Akmal Agus; Azzahra, Maura (Lembaga Yasin AlSys, 2023)
In recent years, an increase in the number of factories and industries has led to an increase in the emission of pollutants into the atmosphere. One of the areas affected by air pollution is Wonorejo, Selomerto sub-district, Wonosobo district, where factories have become the main source of air pollution. This study aims to determine the impact of industrial factory smoke PT. Multi Energi Biomass, a company located in Wonorejo village, Selomerto sub-district, Wonosobo district regarding the condition of the surrounding community. The research method used is a descriptive approach by collecting data through literature studies and interviews with local communities. Data were obtained through structured interviews using a question guide covering perceptions, impacts, countermeasures, and problems encountered. In addition, field observations were made to directly observe factory activities, smoke emissions, and interactions with the surrounding environment. The results of the study revealed that the smoke from PT. Biomass Multi Energy, which is located in Wonorejo village, Selomerto sub-district, Wonosobo district, can have a negative impact on the health and quality of life of the surrounding community. Because smoke emissions are issued in the chimney at the factory continuously. Communities around the industrial factory of PT. Multi Energi Biomass, has made a number of efforts in overcoming air pollution due to the smoke from the industrial factory of PT. Biomass Multi Energy.